Enhanced Bio-Inspired Algorithm With Pedestrian Simulation For Spatial Layout Design - Ibrahim, Najihah (2023)
This research aims to construct an autonomous spatial layout arrangement optimization that can effectively maximize space utilization without compromising the design standard and enhance pedestrian mobility, particularly in emergencies.